RELATED FACTORS TO CLEAN AND HEALTHY LIVING BEHAVIOR AT SD NEGERI 1 RONGA RONGA, GAJAH PUTIH SUBDISTRICT, BENER MERIAH REGENCY - Mashuri, Evan; Santi, Tahara Dilla; Laweung, Ibrahim (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Aceh, 2025)
Background: The health status of students is currently still considered inadequate, as many health problems persist, particularly among school-aged children. One of the major issues is poor clean and healthy living behavior (PHBS). This study aims to identify the factors associated with clean and healthy living behavior (PHBS) at SD Negeri 1 Ronga-Ronga, Gajah Putih Subdistrict, Bener Meriah District. Method: This research is a descriptive-analytic study using a cross-sectional design, with a sample size of 63 students. Primary data were collected through interviews with respondents, while secondary data were obtained from the Aceh Health Office, local health centers, and relevant literature. Data were analyzed using the Chi-square test. Result: The study showed that 52.4% of students had poor PHBS, 54.0% had low knowledge, 57.1% demonstrated negative attitudes, 61.9% indicated a significant role of teachers, and 65.1% acknowledged parental involvement. Bivariate analysis revealed a significant relationship between knowledge and PHBS (p=0.001), attitude and PHBS (p=0.001), teacher's role and PHBS (p=0.021), and parental role and PHBS (p=0.004). Recommendation: It is recommended to further develop and strengthen existing health programs, such as PHBS, by integrating the establishment of